Stabilization of Effluent Treatment Plants Generated Nickel Sludge by Thermo-Chemical Treatment - Kumar Pandey, Sanjay; Gadgil, Kasturi (Asian Journal of Chemistry, 2016)
Metal finishing industries, in their effluent treatment plants (ETP) produce sludge containing heavy metals. These are categorized as toxic solid wastes and hence need special disposal. In the present work experimental studies have been conducted on Ni-bearing ETP sludge to find out the feasibility of stabilization/fixation by thermochemical treatments to non-leachable detoxified form so that when disposed on land, there should be no leachability of nickel either to the soil matrix or seepage to ground water.